INFORMATION AND COMMUNICATION TECHNOLOGIES AIMED AT INTELLECTUAL NATION FORMATION - Sultanbayeva, G. S.; Yanchuk, V. A.; Sultanbayeva, E. S.; Amirzhanova, G. Y. (Farabi Journal of Social Sciences, 2018)
The purpose of this study is to examine the role of information and communication technology (ICT) in enhancing community outreach, academic and research collaboration, and education services in an academic setting. The main aim of the study is to analyze the current ICT development trend in the formation of intellectual nation in Kazakhstan. The formation of “intellectual nation” is a way of modernization of society in the XXI century, when a creative person becomes the main source of development. For Kazakhstan, like for other developing countries, the most important strategic task is to conduct an overall modernization, under which not only institutions and mechanisms of modern society, but also the modern society itself will be created. Questionnaire development was initiated by asking participants involved in community outreach, academic, research, education, and support to provide feedback on current ICT issues and future recommendations for relevant ICT too.